Wireless Sensor Network for Automated Irrigation System in Tea Gardens - Pradhan, Yashu; Deka, Manoj Kumar (International Journal of Computer Sciences and Engineering, 2025)
The aim of this paper is to propose a wireless sensor network in tea garden to show the path to tea gardeners to replace some of the traditional irrigation technique. The present paper focuses on set of technical skills environments to overcome technical backwardness present in traditional tea garden in terms of Moisture level and PH value of soil. This paper describes the technical analysis background for development of expert moisture sensor equipped with monitoring and recording system for real time data of tea gardens soil pH in details. The present study introduces about the parameters to be considered for the design of soil moisture sensor & PH value monitoring system. The cost effectiveness of the sensor/s to be developed and its future perspective of use will depend upon the considering parameters. This paper emphasis only on basic evaluation before development of soil moisture sensor, manageable and workable in tea gardens with minimum cost of production.